SISTEM INFORMASI PASAR (MARKETPLACE) SPAREPART MOTOR CLASSIC BERBASIS WEB - muhyi, ahmad; Martinus, Agust Isa; Triono, Wahyu (INTI TALAFA, 2024)
Economic growth in Indonesia, which has been quite good in the last 10 years, which has increased by an average of around 5% from 2017, has encouraged the economic and industrial sectors to grow quite well. The industry that is growing quite well in Indonesia is in the transportation sector, namely the motorcycle industry. The economic growth of the transportation sector started with the trend of young people who have a hobby in automotive, motorcycles. The trend of modifying vehicles is that there are various types of modifications, starting from the initial condition of the vehicle to changing the desired conditions and modifications to restore the originality of a vehicle or can be called restoration. The trend of modifying classic motorbikes is no less popular among young people, this trend is a trend that is not seasonal. Classic motorbikes themselves are vehicles that were produced in the 90s with various types of brands and various origins of production countries. The challenges of owning a classic motorbike are limited spare parts, a way of driving that is considered impractical and some of the difficulties that actually become an attraction for classic motorbike hobbyists. With the rapid economy in the motorcycle industry sector, it is an opportunity for people to open a business in this sector. The existing marketplaces are general in nature, only providing new motorcycle spare parts and these classic motorcycle spare parts are rarely seen in the available marketplaces. Keywords: Information System, Motorcycle Sparepart, Marketplace, Sale